ESTIMASI NILAI INTRINSIK SAHAM PT KIMIA FARMA TBK. DALAM RANGKA MERGER DENGAN PT INDOFARMA TBK. TAHUN 2012 - , Budi Waluyo ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is aimed to estimate intrinsic value of the equity of PT Kimia Farma in order to merge with PT Indofarma by using discounted cash flow method (DCF) and relative valuation method. The research has become interesting to do because for the event of privatization, PT Kimia Farma Tbk. Has a value that will be a benchmark value on its share offering process, to avoid decreasing income because its stock price which is too low, as well as if it is too high to sell to the public. The data used in this research consists of its financial report at 2007-2011, annual report, comparable companyâs financial report, comparable companyâs stock price, risk free rate, and other supporting data. The analysis used is DCF methods which go with the following steps: sales or earnings projection analysis, financial statement projection, free cash flow projection, discount rate (WACC) determination and value estimation. Relative valuation method was started by determining comparable company on the industry, followed by choosing and determining the multiples wich will be used to converse book value on relevant variable on PT Kimia Farma Tbk. to be estimation of market value of equity. The multiples used are: PER (Price Earning Ratio), PBV (Price to Book Value) and P/S (Price to Sales). The result of the research shows that its intrinsic value of the equity of PT Kimia Farma Tbk. is Rp3.193.125.000.000,00. The value was obtained from reconsiliation process, based on DCF method is Rp3.353.921.406.908,00 and on relative valuation method is Rp3.085.927.247.000,00.